1992
DOI: 10.1002/jcp.1041500310
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive intestinal peptide and forskolin regulate proliferation of the HT29 human colon adenocarcinoma cell line

Abstract: Although several lines of evidence implicate cAMP in the regulation of intestinal cell proliferation, the precise role of this second messenger in the control of the human colon cancer cell cycle is still unclear. In order to investigate the role of cAMP in HT29 cell proliferation, we have tested the effect of vasoactive intestinal peptide (VIP) and forskolin on DNA synthesis and cell number, focusing on the time-dependent efficacy of the treatment. The cells were arrested in G0/G1 phase by incubation for 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…Indeed, the VPAC1 receptor coupling to both adenylyl cyclase and phospholipase C has been demonstrated in certain cell types [18], and cAMP analogs, such as 8-Cl-or N 6 -benzyl-cAMP, were found to inhibit the growth of several human colon cancer cell lines, including HT29 [19]. This inhibition was due to delayed G1/S transition and a reduced rate of DNA synthesis rather than a cytotoxic effect [17]. Dose-related inhibition of cell proliferation by VIP and concentration-dependent increases in cAMP induced by VIP were reported [13,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the VPAC1 receptor coupling to both adenylyl cyclase and phospholipase C has been demonstrated in certain cell types [18], and cAMP analogs, such as 8-Cl-or N 6 -benzyl-cAMP, were found to inhibit the growth of several human colon cancer cell lines, including HT29 [19]. This inhibition was due to delayed G1/S transition and a reduced rate of DNA synthesis rather than a cytotoxic effect [17]. Dose-related inhibition of cell proliferation by VIP and concentration-dependent increases in cAMP induced by VIP were reported [13,15].…”
Section: Discussionmentioning
confidence: 99%
“…Although little is known about the role of VIP as a mediator of normal and neoplastic pancreatic duct cell growth, VIP clearly regulates the growth of other normal and neoplastic cells. VIP inhibits the growth of small cell lung cancer [15], neuroblastoma cells [16], gastric carcinoma cells [12], and colonic adenocarcinoma cells in vitro [17]. The ability of VIP to inhibit cell growth appears to be linked to adenylyl cyclase activation.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the signal transduction pathways and the nuclear factors involved in either the normal, quiescent or the activated, proliferating phenotype of hepatic stellate cells. Because stimulation of the cyclic adenosine 3 Ј ,5 Ј monophosphate (cAMP)-dependent protein kinase (PKA) 1 inhibits proliferation of some tumoral cell lines (13)(14)(15), we analyzed the potential role of this signal transduction pathway on stellate cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have demonstrated that several intestinal regulative peptides have a significant role in regulating the proliferation and growth of epithelial intestinal cells; these molecules are also involved in regulating immunological responses; both proliferation and immune defense are important in the development and growth of CRC [319,320,321,322,323,324].…”
Section: Role Of Regulative Peptides In Intestinal Cancermentioning
confidence: 99%